The Impacts of Professional Skills, Attitude, Time Management and Work Experience on Job Performance: The Case of Mongolia - Bayasgalan, Tsogtsuren; Nomin, Batkhuu (Advances in Social Sciences Research Journal, 2022)
The aim of this study is to analyze the requirements for the impacts of professional skills, professional attitude, work experience on job performance in entrepreneurships. There are many scholars studied the relationship factors on performance management in the world, but there are lack of study our topic in Mongolian private sector such as entrepreneurships. Thus, we interested this topic in here. Performance management, job performance are involve the process of all activities which occurs between an employer and an employee as support of accomplishing value, mission, vision and main objectives in the organization. We collected from 146 employees who work in entrepreneur of Mongolia. The result of data determined through online in first quarter 2022. Our study from many others is we analyzed 4 hypotheses, one of them had a positive relationship with considered impacts. On the other hand, three hypotheses could not have positive relationship on considered impacts. Data was estimated by SPSS 21 and Smart PLS 2.0 statistic programs.